The clarification of the concept of colostomy nursing care in ostomy care centers: A concept analysis through Walker and Avant's method - Maryam Shoja; Narges Arsalani; Masoud Fallahi-Khoshknab; Farahnaz Mohammadi-Shahboulaghi; Shima Shirozhan (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Specialist nurses need to have an accurate understanding of colostomy care-related concepts to provide care. Although patients with different types of ostomy have different types of needs, terms such as ostomy care, colostomy care, and ileostomy nursing are interchangeably used. Moreover, there are limited concept analysis studies into the concept of colostomy nursing care (CNC) in ostomy care centers (OCCs). The aim of this study was to analyze and clarify the concept of CNC in outpatient OCCs. METHODS AND MATERIAL: This was a concept analysis study. This concept analysis was conducted using Walker and Avant's eight-step method. The online databases were searched until 2022 to retrieve documents on CNC. Finally, 35 articles and four books were included in the analysis, the defining attributes, antecedents, and consequences of the concepts were determined, and model and additional cases as well as empirical referents were presented. RESULTS: The defining attributes of CNC in OCCs are the development of professional role, participatory practice and interdisciplinary care, selection of the best clinical procedures, care based on patient education, and patient rehabilitation. The antecedents of the concept are nurse-related antecedents, patient- and family-related antecedents, environmental antecedents, and professional rules and regulations. Its consequences are patients' and families' greater care-related knowledge, improvement of nurses' care quality, patient autonomy, and self-efficacy. CONCLUSION: The concept of CNC in OCCs can be defined as "a continuous and coherent care based on knowledge, skill, expertise, experience, and colostomy type which uses interdisciplinary collaboration and the best available evidence in order to select and provide the best services according to patients' and families' culture and background, fulfill patients' physical, mental, sexual, social, and spiritual needs, and timely refer patients to specialists, with the ultimate goal of improving patient autonomy and facilitating their return to normal life."